Navigating the tension between official and unofficial History – a teacher’s view (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Growing up in the post-apartheid era in a township on the outskirts of Durban, and schooling in Durban North, I always wondered why the houses in KwaMashu township were small, clustered and all looked similar compared to the houses where I schooled. Although I grew up questioning this, I would never discuss such topics with my parents. So, when the topic of apartheid was taught in school “it all made sense” until I did an oral history project on my grandmother, Sibukeli Angelina Mbokazi, who was a domestic worker during the apartheid regime. My grandmother felt differently from what I thought she would, which severely challenged me. This was especially the case because my grandmother and my mother were victims of the apartheid era land dispossession laws. This article articulates the internal challenges I have faced in the history classroom when the unofficial history of my family, as articulated by my grandmother, conflicted with the official curricula and textbooks.
Keywords: Competing discourses; Apartheid; Group Areas Act; Land Act; History; Teaching; Learning